The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1167/iovs.17-21543
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Visually Evoked Functional and Blood Flow Changes in the Rat Retina Measured With a Combined OCT+ERG System

Abstract: PURPOSE. To correlate visually evoked functional and blood flow changes in the rat retina measured simultaneously with a combined optical coherence tomography and electroretinography system (OCTþERG).METHODS. Male Brown Norway (n ¼ 6) rats were dark adapted and anesthetized with ketamine/xylazine. Visually evoked changes in the retinal blood flow (RBF) and functional response were measured simultaneously with an OCTþERG system with 3-lm axial resolution in retinal tissue and 47-kHz image acquisition rate. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…By providing excellent sectioning capability, optical coherence tomography (OCT) provides a noninvasive method to differentiate individual retinal layers . Functional OCT imaging has been explored to achieve depth‐resolved IOS imaging of the retina . However, it is still challenging to achieve selective mapping of neural‐IOS and hemodynamic‐IOS changes.…”
Section: Introductionmentioning
confidence: 99%
“…By providing excellent sectioning capability, optical coherence tomography (OCT) provides a noninvasive method to differentiate individual retinal layers . Functional OCT imaging has been explored to achieve depth‐resolved IOS imaging of the retina . However, it is still challenging to achieve selective mapping of neural‐IOS and hemodynamic‐IOS changes.…”
Section: Introductionmentioning
confidence: 99%
“…A research-grade, spectral domain OCT system, designed and built by our group for various imaging studies in the animal retina [15][16][17] was modified for use in this study. Briefly, a broad bandwidth superluminescent diode (λ c ¼ 1060 nm, Δλ ¼ 110 nm, Superlum Ltd., Ireland) was used to achieve 3. , was designed to deliver a collimated imaging beam of 1.5 mm diameter to the rat cornea, thus achieving ∼5-μm lateral resolution in retinal tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The OCTþERG system was developed by our research group for various animal retinal studies [36][37][38] and was recently used to evaluate the effect of single-flash and flicker stimuli on the total axial RBF. 34 In this study, a different scanning protocol was used in order to evaluate the total retinal blood flow (TRBF) before, during, and after IOP elevation. Briefly, the OCT system operates in the 1060-nm spectral region and provides~3-lm axial and~5-lm lateral resolution in the rat retina, at 92-kHz image acquisition rate.…”
Section: Octþerg Systemmentioning
confidence: 99%
“…[29][30][31][32][33] Recently, our research group has developed a combined OCTþERG system that allows for examination of the neurovascular coupling in the rat retina. 34 A study conducted with this system in healthy rats under normal IOP showed that flicker-induced changes in the RBF are time-correlated with amplitude and latency changes of the ERG traces.…”
mentioning
confidence: 99%